Model Pengembangan Diri Siswa melalui Budaya Religius (Religious Culture) di Sekolah Menengah Kejuruan Teknologi Informasi (SMK TI) - Karmila, Karmila (SYAMIL: Journal of Islamic Education, 2014)
SMK IT Airlangga Samarinda tries to develop themselves with the religious culture in order to create students who have a scientific qualifications, skills, good morals in life and able to compete with others. The purpose of this research is 1). To determine the values of the religious culture in SMK IT Airlangga Samarinda, and 2). To determine the model of self-development through the religious culture) in SMK IT Airlangga Samarinda. The kind of this research is qualitative descriptive. Informants in this study were the Principal, Deputy, Teachers and Students of SMK IT Airlangga Samarinda. Data were analyzed by following the model of Miles and Huberman. From the analysis of the data, we concluded that: 1). Forms of cultural practice of religious activities in schools, among them; familiarize greeting when meeting teachers, shaking hands, praying. 2). Personal Development Model through Religious Culture in SMK IT Airlangga Samarinda that some extracurricular activities developed in the framework of self-development through the religious culture.